Rancang Bangun OwnCloud Sebagai Cloud Storage di Kampus STMIK PPKIA Tarakanita Rahmawati - Hadriansa, Hadriansa; Prayogi, Denis; Harianto, Kandi (STMIK Budi Darma, 2020)
Media storage based on cloud computing is now widely used as a solution for exchanging data and information in an institution to support work. At STMIK PPKIA Tarakanita Rahmawati, cloud-based storage is very necessary because many data and information exchange activities are carried out digitally, both data exchange between lecturers, academic community, education staff and students. Utilization of ownCloud as an open source software to solve the problem of cloud computing-based data exchange is very appropriate because the website-based, desktop and mobile-based applications make it easier for users to access data. Â Owncloud is similar to applications like Google Drive, Dropbox, it's just that all settings and data processing and user can be done independently so that it can adjust to the needs. The results of this research, Owncloud can be used well by lecturers to store data related to lectures and research, students to store lecture data centrally, the academic community in storing data related to academic activities. The design of owncloud is also still done intranet, so to access it must be connected to the network around the campus of STMIK PPKIA Tarakanita Rahmawati